Development of Arithmetic Rows and Series Learning Media in Malay Islam Context - Saputrama, Rendi; Fitrianti, Yuli; Ramury, Feli (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
This study aims to produce computer-based mathematics learning media using the Adobe Animate CC application on arithmetic sequences and series material in the context of Malay Islam with valid and prismatic categories. This type of research is design research in the development study section of the Akker method with the Tessmer procedure which consists of a preliminary stage and a prototyping stage with a formative evaluation flow (self-evaluation, one-to-one, small group, and field test stages). The research subjects were students of class XI MA Aulia Cendekia Palembang. The results show that the learning media developed is valid and practical.Penelitian ini bertujuan untuk menghasilkan media pembelajaran matematika berbasis komputer menggunakan aplikasi Adobe Animate CC pada materi barisan dan deret aritmetika dalam konteks Islam Melayu dengan kategori valid dan priaktis. Jenis penelitian ini adalah design research pada bagian development study metode Akker dengan prosedur Tessmer yang terdiri dari tahap preliminary dan tahap prototyping dengan alur formative evaluation (tahap selft evaluation, one-to-one, small group, dan field test). Subjek penelitian adalah siswa kelas XI MA Aulia Cendekia Palembang. Hasil menunjukkan bahwa media pembelajaran yang dikembangkan valid dan praktis.